Risk factors in therapeutic interventions and treatment of acute myocardial infarction - Garcia Lasluiz , Melany Michell (2025)
Acute myocardial infarction (AMI) is a serious medical event that results from the death of heart tissue due to lack of blood flow, usually caused by blockage of a coronary artery. The objective of this article is to evaluate, from a documentary review, the risk factors in therapeutic interventions and treatment of acute myocardial infarction. It was oriented towards the quantitative research approach; documentary type, with a non-experimental design and the positivist paradigm. A thorough exploration of scientific documents and articles was carried out using databases such as Scielo, Dialnet, UptoDate, Pubmed, Elsevier, among others. The results were that lifestyle contributes significantly to the risk of heart attack. It is concluded that, regarding unhealthy habits, such as smoking, excessive alcohol consumption and a diet high in cholesterol, they are significantly associated with the risk of AMI